Kunitz Proteinase Inhibitors Limit Water Stress Responses in White Clover (Trifolium repens L.) Plants - Islam, Afsana; Leung, Susanna; Nikmatullah, Aluh; Dijkwel, Paul P.; McManus, Michael T. (Frontiers in Plant Science, 2017)
The response of plants to water deficiency or drought is a complex process, the perception of which is triggered at the molecular level before any visible morphological responses are detected. It was found that different groups of plant proteinase inhibitors (PIs) are induced and play an active role during abiotic stress conditions such as drought. Our previous work with the white clover (Trifolium repens L.) Kunitz Proteinase Inhibitor (Tr-KPI) gene family showed that Tr-KPIs are differentially regulated to ontogenetic and biotic stress associated cues and that, at least some members of this gene family may be required to maintain cellular homeostasis. Altered cellular homeostasis may also affect abiotic stress responses and therefore, we aimed to understand if distinct Tr-PKI members function during drought stress. First, the expression level of three Tr-KPI genes, Tr-KPI1, Tr-KPI2, and Tr-KPI5, was measured in two cultivars and one white clover ecotype with differing capacity to tolerate drought. The expression of Tr-KPI1 and Tr-KPI5 increased in response to water deficiency and this was exaggerated when the plants were treated with a previous period of water deficiency. In contrast, proline accumulation and increased expression of Tr-NCED1, a gene encoding a protein involved in ABA biosynthesis, was delayed in plants that experienced a previous drought period. RNAi knock-down of Tr-KPI1 and Tr-KPI5 resulted in increased proline accumulation in leaf tissue of plants grown under both well-watered and water-deficit conditions. In addition, increased expression of genes involved in ethylene biosynthesis was found. The data suggests that Tr-KPIs, particularly Tr-KPI5, have an explicit function during water limitation. The results also imply that the Tr-KPI family has different in planta proteinase targets and that the functions of this protein family are not solely restricted to one of storage proteins or in response to biotic stress.